Analysis of Financial Performance of Village Fund Allocation Management Based on The Effectiveness Ratio and Growth Ratio at the Village Office Klambir District Hamparan Perak - Echa Elzha Fitri; Oktarini Khamilah Siregar (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
allocation management at the Village Office Klambir district Hamparan Perak based on the effectiveness ratio and growth ratio during the period 2020 to 2023. The method used in this research is descriptive quantitative, with the use of data through library studies and documentation of financial statements of the village. The result of this study indicate that the financial performance of the village categorized effective, with the average effectiveness ratio reached 98,71%. However, the growth ratio for both revenue and expenditure exhibit fluctuations, with an average revenue growth ratio of 13,00% and an expenditure growth ratio of 6,40%. This study recommends enhancing financial management, providing training for village officials, and diversifying revenue sources to improve the independence and sustainability of village finances. The result of this research are expected to contribute to the development of knowledge in the field of village finance and serve as a reference for future studies